Patient-reported aesthetic outcomes of upper blepharoplasty: a randomized controlled trial comparing two surgical techniques. Issue 9 (September 2022) - Hollander, M.H.J.; Delli, K.; Vissink, A.; Schepers, R.H.; Jansma, J.
Abstract: It is not yet established whether additional orbicularis oculi muscle excision leads to better patient-reported aesthetic outcomes (PRO) compared to a skin-only resection blepharoplasty. A double-blind randomized controlled trial of upper blepharoplasty, with or without muscle excision, was performed on 54 White European patients who assessed the procedure via PRO. FACE-Q questionnaires covering eyes in general, upper eyelids, forehead and eyebrows, overall face, age appearance appraisal, age appraisal, social functioning, satisfaction with the outcome, and adverse effects were completed preoperatively and at 6 and 12 months after upper blepharoplasty. The Patient and Observer Scar Assessment Scale was used to assess scarring. The FACE-Q scores for skin-only and skin/muscle upper blepharoplasty were similar regarding the upper eyelids, forehead and eyebrows, overall face, patient perceived aging and age, social functioning, and satisfaction with the results, and also increased for both procedures with time. The FACE-Q score regarding the eyes in general was higher in the skin-only group at the 12-month follow-up. Scarring and adverse effects did not differ between the groups. Additional muscle resection does not seem to influence patient satisfaction. Thus, when performing an upper blepharoplasty, there is no need for additional muscle resection as a routine procedure to improve patient satisfaction.